Electronic and solvent effects on monosaccharide conformations - Barnett_CB (Department of Chemistry, 2024)
The hydroxymethyl group rotational preferences of the monosaccharides glucose and galactose are different from each other and non-intuitive (from a steric point of view) in their preferences for gauche conformers. These molecules exhibit very different biological and thermodynamic properties in, for example their binding to glycosides or their liquid crystalline phases in glycolipids. The preference for gauche conformations has been attributed to solvent effects, stereoelectronic effects and hydrogen bonding; yet the experimentally obtained hydroxymethyl rotational populations have not yet been fully rationalised. In this dissertation, I have used a range of ab initio, Molecular Dynamics (MD), Quantum Mechanics/Molecular Mechanics (QM/MM) and free energy computational methods to resolve and explain this observation. The hydroxymethyl free energy surface was calculated using the Potential of Mean Force (PMF), umbrella sampling and Weighted Histogram Analysis Methods (WHAM). The PMF calculations were performed in the canonical (NVT) ensemble in the gaseous and aqueous phase where each monosaccharide was modelled with Parameter Model 3 for Carbohydrates (PM3CARB-I). Density Functional Theory (OFT) calculations were also carried out and Atoms in Molecules (AIM) and Natural Bond Orbital (NBO) analyses were applied. Gaseous phase simulation results for both glucose and galactose gave hydroxymethyl rotational preferences of gg>tg>gt and gt>gg>tg respectively. These confrontational preferences can be rationalised in terms of an intrinsic stereoelectronic effect (found from NBO calculations) and strong intramolecular hydrogen bonding (found in the tg conformer of glucose and the gg conformer of galactose using AIM) in the gaseous phase. The addition of solvent (water) was found to disrupt the intramolecular hydrogen bonding present in the gaseous phase. Hydroxymethyl rotational preferences in the solution phase were gg>gt>tg for glucose and gt>tg>gg for galactose. The population distributions in solution were also calculated for glucose as gg:gt:tg = 59.21 :34.88:0.83 and for galactose as gg:gt:tg = 3.32:79.60: 1 0.15. These populations agree favourably with experimental NMR populations. The solvent conformational preference is dominated by the intrinsic stereoeIectronic effect and steric interactions. The gauche effect in monosaccharides has been successfully rationalised.